SUPERVISED TEACHING PRACTICE IN PHYSICAL EDUCATION: THE MOBILIZATION OF TEACHER KNOWLEDGES - Carvalho, Taynara Franco De [UNESP]; Souza, Samuel De [UNESP] (Universidade Estadual de Maringá, 2019)
This work focuses on the training of physical education teachers in the Supervised Teaching Practice. It aims to understand the knowledges that are mobilized in the Supervised Teaching Practice. The qualitative research, descriptive study, using as techniques: interview with 10 trainees and seven teachers and content analysis. The participants pointed out that the construction of the knowledges and the rescue of the experiences are continuous, having as influences the schooling, the teaching practice and the training courses. The mobilization of the disciplinary, curriculum, pedagogical tradition and pedagogical action knowledges by students in the internship occurred according to the needs and challenges of this process, forming a kind of reservoir. From this reservoir of knowledges, teachers mobilize the experiential knowledge (an amalgam of knowledges) in the supervision and guidance of the internship. In this knowledge base, the teacher is supplied, while the student is guided in the practice of teaching.

Este trabalho focaliza a formação de professores de Educação Física no Estágio Supervisionado. Ele tem como objetivo central compreender os saberes que são mobilizados no Estágio Supervisionado. Opta-se pela pesquisa qualitativa, estudo descritivo, utilizando como técnicas: entrevista com 10 estagiários e sete professores e análise de conteúdo. Os participantes apontaram que a construção dos saberes e o resgate das experiências são contínuas, tendo como influências a escolarização, a prática docente e a realização de cursos. A mobilização dos saberes (disciplinar, curricular, tradição pedagógica, ação pedagógica) pelos estudantes no estágio ocorreu de acordo com as necessidades e desafios desse processo, formando uma espécie de reservatório. Desse reservatório de saberes, os professores mobilizam o saber experiencial (uma amálgama de saberes) na supervisão e orientação do estágio. Nessa base de conhecimento, o professor se abastece, enquanto o estudante se orienta na prática de ensino.
ESTÁGIO SUPERVISIONADO NA EDUCAÇÃO FÍSICA: A MOBILIZAÇÃO DOS SABERES DOCENTE
Keywords: Supervised teaching; Knowledge teachers; Initial teacher education; Estágio supervisionado; Saberes docentes; Formação inicial